2014
DOI: 10.1371/journal.pone.0101555
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Palmitate Treatment of Myotubes from Postmenopausal Women Leads to Ceramide Accumulation, Inflammation and Affected Insulin Signaling

Abstract: Menopause is associated with an increased incidence of insulin resistance and metabolic diseases. In a chronic palmitate treatment model, we investigated the role of skeletal muscle fatty acid exposure in relation to the metabolic deterioration observed with menopause. Human skeletal muscle satellite cells were isolated from premenopausal (n = 6) and postmenopausal (n = 5) women. In an in vitro model, the myotubes were treated with palmitate (300 µM) for one-, two- or three days during differentiation. Effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Our study also showed that FA pretreatment could significantly decrease the mRNA expression of NFκB (Fig. 5A), similar to the results of Abildgaard et al [28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study also showed that FA pretreatment could significantly decrease the mRNA expression of NFκB (Fig. 5A), similar to the results of Abildgaard et al [28].…”
Section: Discussionsupporting
confidence: 92%
“…Abildgaard et al [28] proved that palmitate-treated myotubes showed increased phosphorylation of JNK. Our results also showed that PA treatment could upregulate the phosphorylation of JNK, which positively correlated with the severity of IR (p-JNK/JNK).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies revealed that the accumulation of lipid intermediates in peripheral tissues, mainly muscle tissue, leads to low fat oxidation and altered fatty acid metabolism through increased inflammatory pathway [30]. In this way, an in vitro study with myotubes from postmenopausal women treated with fatty acid leads to ceramide accumulation and inflammation, reducing insulin signaling [31]. Here, we believed that the higher CRP levels identified in MUO postmenopausal women in our study may contribute to low fat oxidation rate during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Women have greater insulin‐stimulated leg glucose uptake than matched men despite having higher intramyocellular triacylglycerol content (Hoeg et al, ), whereas increasing lipid levels through lipid infusion results in less insulin resistance of skeletal muscle glucose uptake in women than men (Hoeg et al, ). Interestingly, skeletal muscle cells from premenopausal women (high‐oestrogen environment) showed a lower stress response after prolonged in vitro fatty acid (palmitate) treatment compared with skeletal muscle cells from postmenopausal women (low‐oestrogen environment; Abildgaard et al, ). Although Torres et al () recently showed that oestrogen has a direct impact on the mitochondrial membrane viscosity and improves bioenergetic function of the mitochondrion, suggesting that the sex‐mediated differences in lipid tolerability could be partly mediated by oestrogen.…”
Section: Sex Differences In Inflammatory‐related Metabolic Syndromementioning
confidence: 99%